Strategi Pengembangan Ekowisata Hutan Mangrove Di Darunu Mangrove Park Kecamatan Wori Kabupaten Minahasa Utara - Hutabarat, Silsilia; Kapantow, Gene Henfried Meyer; Baroleh, Jenny (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
The research aims to examine the Mangrove Forest Ecotourism Development Strategy in Darunu Mnagrove Park, Wori District, North Minahasa Regency. The research took place for one month from April to May 2024. The sampling method in this research is Purposive Sampling and Accidental Sampling. The sampling methods in this study are Purposive Sampling and Accidental Sampling. The data used are primary data and secondary data. Primary data were obtained from FGD interviews and observations. Meanwhile, secondary data is obtained from the internet and other sources in the form of documents from village officials. The analysis method used in this study is a SWOT analysis to answer the strategy of ecotourism development of Mangrove Forest in Darunu Mangrove Park,, North Minahasa Regency. The results of the study show that based on SWOT analysis, the strategy for the development of mangrove forest ecotourism in Darunu Mangrove Park is in quadrant I, meaning that the aggressive strategy is by prioritizing the SO (Strength – Opportunity) strategy, including holding mangrove tour ecotourism activities, maintaining the habitat of marine fauna, utilizing huts or gazebos for educational activities, and encouraging local communities to be more actively involved in tourism management.